Handbook of research on resource management for pollution and waste treatment - Affam, Augustine Chioma, 1979-; Ezechi, Ezerie Henry, 1983- (Advances in environmental engineering and green technologies (AEEGT) book series., 2020)
"This book examines resource management strategies for waste and pollution treatment methods"--